2001
DOI: 10.1056/nejmoa010746
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Clopidogrel in Addition to Aspirin in Patients with Acute Coronary Syndromes without ST-Segment Elevation

Abstract: Background Despite current treatments, patients who have acute coronary syndromes without ST-segment elevation have high rates of major vascular events. We evaluated the efficacy and safety of the antiplatelet agent clopidogrel when given with aspirin in such patients. MethodsWe randomly assigned 12,562 patients who had presented within 24 hours after the onset of symptoms to receive clopidogrel (300 mg immediately, followed by 75 mg once daily) (6259 patients) or placebo (6303 patients) in addition to aspirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
728
0
17

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 5,640 publications
(756 citation statements)
references
References 16 publications
11
728
0
17
Order By: Relevance
“…Platelet P2Y 12 receptor inhibitors have been a cornerstone of treatment for patients with acute coronary syndrome; both clopidogrel and higher potency P2Y 12 inhibitors (prasugrel and ticagrelor) were shown to significantly reduce the risk of major adverse cardiovascular events 1, 2, 3. Yet, the optimal timing of administration of P2Y 12 inhibitors has been a moving target for patients with non‐ST‐elevation myocardial infarction (NSTEMI).…”
Section: Introductionmentioning
confidence: 99%
“…Platelet P2Y 12 receptor inhibitors have been a cornerstone of treatment for patients with acute coronary syndrome; both clopidogrel and higher potency P2Y 12 inhibitors (prasugrel and ticagrelor) were shown to significantly reduce the risk of major adverse cardiovascular events 1, 2, 3. Yet, the optimal timing of administration of P2Y 12 inhibitors has been a moving target for patients with non‐ST‐elevation myocardial infarction (NSTEMI).…”
Section: Introductionmentioning
confidence: 99%
“…Given hematological side effects associated with ticlodipine, clopidogrel, another member of the thienopyridine family, became an attractive alternative. The CURE (Clopidogrel in Unstable Angina to Prevent Recurrent Events) trial showed a 30% reduction in major adverse cardiovascular events when clopidogrel was added to aspirin for treatment of patients presenting with non‐ST‐segment elevation acute coronary syndrome 4. Additionally, within a subset of patients in the CURE trial who were randomized to pretreatment with clopidogrel, results showed the benefits of clopidogrel within 24 hours of randomization and extending long term, without increased bleeding risk 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…As may be expected, the increasing potency of the P2Y12 inhibitors has been accompanied by a higher risk of bleeding, including procedure‐related bleeding. Even when clopidogrel, the least potent of the P2Y12 inhibitors, was added to aspirin in the CURE study, the bleeding risk was significantly higher than with aspirin alone 4. Similarly, with the progressive increase in potency of P2Y12 inhibitors, bleeding risk has increased—compared with clopidogrel, prasugrel caused increased risk of bleeding, including life‐threatening bleeding, and ticagrelor increased the risk of non‐CABG‐related major bleeding 7, 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute myocardial infarction usually occurs as a result of ruptured atherosclerotic plaque, platelet‐mediated thrombosis and prolonged myocardial ischaemia 4, 5. Antiplatelet drug clopidogrel is an appropriate and immediate treatment for AMI, and should be used for long‐term to prevent recurrent ischaemic events 6, 7.…”
Section: Introductionmentioning
confidence: 99%